1988
DOI: 10.1111/j.1600-0528.1988.tb00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Compliance following referral in the early detection of oral cancer and precancer in Sri Lanka

Abstract: An innovative approach for the early detection of oral cancer and precancer within the context of the primary health care system has been field tested in Sri Lanka. The overall compliance in accepting this particular PHC approach for cancer screening, as estimated by arrival at a referral centre manned by consultant staff, was 54.1%. Nearly 80% of those who turned up without needing an additional reminder, did so within the first 2 weeks of case finding. There was a variation in the degree of compliance depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…79,80 Of the remaining 90, agreement was reached for the inclusion of 28 studies. [13][14][15]28,32,34,38,41,46,48,[53][54][55][56]60,64,65,[67][68][69][70][81][82][83][84][85][86][87] The initial kappa score for agreement was reasonable ( = 0.60).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…79,80 Of the remaining 90, agreement was reached for the inclusion of 28 studies. [13][14][15]28,32,34,38,41,46,48,[53][54][55][56]60,64,65,[67][68][69][70][81][82][83][84][85][86][87] The initial kappa score for agreement was reasonable ( = 0.60).…”
Section: Resultsmentioning
confidence: 99%
“…The only long-term large-scale population-based studies in an industrialised country were from Japan. 28,32,46,55,56 All other population-based programmes were carried out in either the Indian subcontinent 53,54,60,64,65,[67][68][69]83 or Cuba 82 and tended to rely on non-professional staff or specifically trained health workers/volunteers to screen large numbers of participants. Methods of recruitment varied from opportunistic to invitational, and targeted populations varied both in terms of age (from 20+ to 60+ years old) and other risk behaviours such as tobacco and alcohol consumption.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Two of these, and the further reports listed in Table 3, provided outcome data on patients referred for secondary care including numbers of individuals screened, numbers referred, numbers who attended, true-and falsepositive rates, and positive predictive values of the test. 9,12,[15][16][17][18][19][20][21] With regard to the findings of the first group of studies (Table 2), sensitivity (Sn) values ranged from 0.60 to 0.95. Specificity (Sp) values were at least 0.94 apart from the Sri Lanka study where the basic health workers returned a false-positive rate of 19% (Sp = 0.81).…”
Section: Resultsmentioning
confidence: 99%
“…12 The reports of Warnakulasuriya and colleagues in Sri Lanka described a similar approach. 13,20,21 The British and Japanese studies employed dentists from various practice settings as screeners, without specific training in the first instance and with training and calibration in the second. On the other hand, the studies in the Indian sub-continent, reflecting the economic circumstances prevailing in that part of the world, investigated the use of specifically trained basic health workers as screeners in a possible relatively low cost preventive strategy for combating their exceptionally high levels of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the rate of hospital attendance by patients identified in this manner was poor 18. The British working group recently concluded that opportunistic screening of patients attending dental surgeries is the most cost effective option in Britain 19…”
mentioning
confidence: 99%